Effect of sacubitril/valsartan on renal function: a systematic review and meta‐analysis of randomized controlled trials - Spannella, Francesco (ESC Heart Fail, 2020)
A worsening renal function is prevalent among patients with cardiovascular disease, especially heart failure (HF). Sacubitril/valsartan appears to prevent worsening of renal function and progression of chronic kidney disease (CKD) as compared with renin–angiotensin system (RAS) inhibitors alone in HF patients. It is unclear whether these advantages are present in HF patients only, or can be extended to other categories of patients, in which this drug was studied. We performed a systematic review and meta‐analysis to assess the consistency of effect size regarding renal outcome across randomized controlled trials (RCTs) that compared sacubitril/valsartan with RAS inhibitors in patients with or without HF. We searched Medline (PubMed), Scopus, and Thomson Reuters Web of Science databases until June 2020. We took into account RCTs that compared sacubitril/valsartan with a RAS inhibitor and reported data regarding renal function. We used random‐effects models to obtain summary odds ratio (OR) with 95% confidence interval (CI). We extracted hazard ratios for renal outcomes, glomerular filtration rate slopes or rates of renal adverse events. Sensitivity analyses were performed by moderator analysis and random‐effects meta‐regression. The search revealed 10 RCTs (published between 2012 and 2019) on 16 456 subjects. Sacubitril/valsartan resulted in a lower risk of renal dysfunction as compared with RAS inhibitors alone [k = 10; pooled OR = 0.70 (95% CI 0.57–0.85); P < 0.001], with a moderate inconsistency between studies [Q(9) = 15.18; P = 0.086; I (2) = 40.73%]. A stronger association was found in studies including older patients (k = 10; β = −0.047730; P = 0.020) or HF patients with preserved ejection fraction [pooled OR = 0.53 (0.41–0.68) vs. 0.76 (0.57–1.01) for studies on HF patients with reduced ejection fraction; P for comparison = 0.065]. The effect size did not change with different comparators (angiotensin‐converting enzyme inhibitors vs. angiotensin II type 1 receptor blockers, P = 0.279). No significant association was found when the analysis was restricted to studies on non‐HF patients [k = 3; pooled OR = 0.86 (0.61–1.22); P = 0.403] and studies with high risk of bias [k = 3; pooled OR = 0.34 (0.08–1.44); P = 0.143]. Our findings support the role of sacubitril/valsartan on preservation of renal function, especially in older patients and HF patients with preserved ejection fraction. However, evidence is currently limited to HF patients, while the renal outcome of sacubitril/valsartan therapy outside the HF setting needs to be further investigated.